LncRNA CRNDE promotes hepatoma cell proliferation by regulating the metabolic reprogramming of M2 macrophages via ERK pathway - Chao Lin; Tao Jiang; Changyong E; Lun Wang; Tong Chen; Xia Wang; Yien Xiang (Cancer Cell International)
Abstract Background LncRNA colorectal neoplasia differentially expressed (CRNDE) was found to be an important regulator in many cancers. This project focuses on the function of CRNDE on macrophage metabolic reprogramming and Hepatocellular carcinoma (HCC). Method qRT-PCR and Immunofluorescence were used to analyze Arg-1, IL-10, CD163, CCL-18, CD206, and CRNDE expression in HCC tissues and macrophages. Western Blotting was used to analyze ERK and p-ERK expression. Edu assay, transwell assay and xenograft experiments were carried out to study cell viability, migrated and invasive capability. Immunohistochemical staining was used to evaluate Ki67 expression. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) was performed for macrophages metabolites analysis. Results Arg-1, IL-10, CD163, CD206, and CRNDE were significantly up-regulated in HCC tissues, M2 macrophage and M0 macrophage with CRNDE overexpressed (OV-CRNDE-M0), which downregulated in M0 macrophage with CRNDE knockdown (sh-CRNDE-M0). The conditioned medium (CM) of M2 cells and OV-CRNDE-M0 cells promoted cell viability, invasion, and migration of HCC cells, the effect was reversed by sh-CRNDE-M0 cells CM. OV-CRNDE-M0 cells promoted tumor growth, Ki67 and CD206 expression in xenograft model. 61 metabolites were detected, of which 18 metabolites changed significantly in OV-CRNDE-M0 group compared to M0 group, with 9 upregulated and 9 downregulated. KEGG analysis showed the enrichment pathways were biosynthesis, glyoxylate and dicarboxylate metabolism. SMPDB analysis showed the enrichment pathways were hypoacetylaspartia, canavan disease, and aspartate metabolism. Conclusion CRNDE regulated the metabolic reprogramming of M2 macrophage via ERK pathway, which thereby contributed to HCC proliferation, migration, and invasion.